Comprehensive genomic profiling of 295 cases of clinically advanced urothelial carcinoma of the urinary bladder reveals a high frequency of clinically relevant genomic alterations. Issue 5 (9th December 2015) - Ross, Jeffrey S.; Wang, Kai; Khaira, Depinder; Ali, Siraj M.; Fisher, Huge A.G.; Mian, Badar; Nazeer, Tipu; Elvin, Julia A.; Palma, Norma; Yelensky, Roman; Lipson, Doron; Miller, Vincent A.; et al.
Abstract : BACKGROUND: In the current study, the authors present a comprehensive genomic profile (CGP)‐based study of advanced urothelial carcinoma (UC) designed to detect clinically relevant genomic alterations (CRGAs). METHODS: DNA was extracted from 40 µm of formalin‐fixed, paraffin‐embedded sections from 295 consecutive cases of recurrent/metastatic UC. CGP was performed on hybridization‐captured, adaptor ligation‐based libraries to a mean coverage depth of 688X for all coding exons of 236 cancer‐related genes plus 47 introns from 19 genes frequently rearranged in cancer, using process‐matched normal control samples as a reference. CRGAs were defined as GAs linked to drugs on the market or currently under evaluation in mechanism‐driven clinical trials. RESULTS: All 295 patients assessed were classified with high‐grade (International Society of Urological Pathology classification) and advanced stage (stage III/IV American Joint Committee on Cancer) disease, and 294 of 295 patients (99.7%) had at least 1 GA on CGP with a mean of 6.4 GAs per UC (61% substitutions/insertions/deletions, 37% copy number alterations, and 2% fusions). Furthermore, 275 patients (93%) had at least 1 CRGA involving 75 individual genes with a mean of 2.6 CRGAs per UC. The most common CRGAs involved cyclin‐dependent kinase inhibitor 2A ( CDKN2A ) (34%), fibroblast growth factor receptor 3 ( FGFR3 ) (21%), phosphatidylinositol 3‐kinase catalytic subunit alpha ( PIK3CA ) (20%), and ERBB2 (17%). FGFR3 GAs were diverse types and included 10% fusions. ERBB2 GAs were equally divided between amplifications and substitutions. ERBB2 substitutions were predominantly within the extracellular domain and were highly enriched in patients with micropapillary UC (38% of 32 cases vs 5% of 263 nonmicropapillary UC cases; P <.0001). CONCLUSIONS: Using a CGP assay capable of detecting all classes of GA simultaneously, an extraordinarily high frequency of CRGA was identified in a large series of patients with advanced UC. Cancer 2016;122:702–711. © 2015 American Cancer Society . Abstract : Advanced urothelial carcinoma is an invariably fatal disease, and there is a lack of effective, approved systemic therapies beyond first‐line platinum‐based chemotherapy. In the current study, the authors identify a high frequency of clinically relevant genomic alterations in a large cohort of patients with advanced disease. Conceivably, these results could inform the rational design of clinical trials of targeted therapies for patients with advanced urothelial carcinoma.